Indexes to Debates of the National Assembly (Hansard) - South Africa Parliament (Cape Town Government Printers, 1996)
South Africa Parliament Debates of the National Assembly.
South Africa Politics and government. Debates of the National Assembly. Continued in part by: Interpellations, questions and replies of the National Assembly. 21 cm
Keywords: Indexes to Debates; National Assembly; Hansard; Third Session - First Parliament; 15 January; 7 November; 1996; Vol. 12; ISBN 0621271152; ISBN 0621271225; JC278423; Index to Speeches